Self-perceived academic stress and related factors in a private dental school from Cartagena, Colombia - Tirado-Amador, Lesbia Rosa; Morales-Vega, José Javier; Vargas-Quiroga, Edgar Daniel; Arce-Vanegas, Jhon Alex (Universidad y Salud, 2023)
Introduction: Academic stress arises from an interaction between environmental stressors and student reactions, which are associated with academic frustration and academic failure. Likewise, there are demographic and family factors that affect stress. Objective: To analyze academic stress, demographic and family factors in Dentistry students at a private school in Cartagena. Materials and methods: A descriptive cross-sectional study with 158 students. The APGAR family sociodemographic questionnaire and SISCO inventory were used. Descriptive statistics and the X2 test were applied to analyze data. Results: Family dysfunction and low friend support were observed in almost half of the participants, 70% displayed moderate anxiety levels. Also, a high frequency of environmental demands (stressors), behavioral reactions, and the presence of symptoms in response to the stressors were found. There were associations between: high frequency of restlessness in everyday situations and belonging to initial semesters; low frequency of using coping strategies and female gender; and high frequency of behavioral reactions and family dysfunction. Conclusions: The main factors identified were belonging to initial semesters, being a woman, and family dysfunction. Levels of stress and family dysfunction can be used as a signal for university welfare services to intervene and prevent unfavorable student health and academic performance conditions.